2018
DOI: 10.3390/toxins10110462
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration and Reuse of Immunoaffinity Column for Highly Efficient Clean-Up and Economic Detection of Ochratoxin A in Malt and Ginger

Abstract: Immunoaffinity columns (IACs) are most popularly used for mycotoxin clean-up in complex matrices prior to chromatographic analysis. But, their high cost has limited their wide application and the regeneration of IACs for multiple instances of reuse is important. This study aimed to investigate the feasibility of regeneration and reuse of IACs for purification of ochratoxin A (OTA) in spiked raw malt and dried ginger samples followed by high performance liquid chromatography-fluorescence detection. After each u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Indeed, despite their susceptibility to irreversible denaturation in some conditions, numerous studies have shown the possibility to reuse ISs after their storage at 4°C in a PBS solution, which is close to physiological conditions and in the presence of an antimicrobial agent such as sodium azide. This possible regeneration was confirmed recently by a detailed study related to the reusability of commercial ISs dedicated to mycotoxin analysis (98). In the same way, despite their sensitivity to nuclease, OSs can be stored at 4°C in a buffer solution, whose composition is close to the binding buffer, and containing also sodium azide.…”
Section: -Reusability Regenerationmentioning
confidence: 77%
“…Indeed, despite their susceptibility to irreversible denaturation in some conditions, numerous studies have shown the possibility to reuse ISs after their storage at 4°C in a PBS solution, which is close to physiological conditions and in the presence of an antimicrobial agent such as sodium azide. This possible regeneration was confirmed recently by a detailed study related to the reusability of commercial ISs dedicated to mycotoxin analysis (98). In the same way, despite their sensitivity to nuclease, OSs can be stored at 4°C in a buffer solution, whose composition is close to the binding buffer, and containing also sodium azide.…”
Section: -Reusability Regenerationmentioning
confidence: 77%
“…In another study, Immunoaffinity column high-performance thin layer chromatography (IM-HPTLC) has also been used to detect OTA with limits of detection <0.28 µg/kg (Chompurat et al, 2007). More recently, an LOD of around 0.4 ng/mL was reported with multitime-regenerated IM (Liu X. et al, 2018). Meanwhile, Yuan et al (2009) reported a rapid and highly sensitive competitive immunoassay coupled to surface plasmon resonance (IM-SPR) for OTA quantification in cereals and beverage.…”
Section: Biological Detection Methods For Otamentioning
confidence: 99%
“…IACs are very sensitive, selective, and can serve as universal and valid purification tool for tracing the mycotoxins. Furthermore, it is a user-friendly and solvent-saving method because of the antibodies’ specificity [ 65 ]. However, some limitations are linked with this technique.…”
Section: Food Sampling and Sample Preparationmentioning
confidence: 99%
“…Other disadvantages include organic solvents, which can denature or devitalize the antibodies leading to difficulties in the reuse of IACs. Moreover, the operating costs of this method are substantially high [ 65 ]. IAC has been successfully applied in simultaneous analysis of OTA, ZEA, and AFs in wheat bran [ 67 ], OTA, AFs, and Fusarium toxins in maize [ 68 ] and cereals [ 69 ].…”
Section: Food Sampling and Sample Preparationmentioning
confidence: 99%